The Influence of Intra Collaboration and Supply Chain Management on Market Performance of MSMEs through Using Information Technology Training - Farida, Eka; Baidlowi, Ridwan (Jurnal Pendidikan Edutama, 2025)
Intra collaboration, supply chain systems, and the use of information technology are milestones that need to be considered to increase micro, small and medium scale businesses in controlling the market. The use of technology is an important part that supports the marketing work process to achieve market performance for MSME products. This study aims to measure the market performance of MSMEs in terms of intra collaboration and supply chain management mediated through using IT training. The research method uses quantitative methods with an explanatory research approach. The research data source is primary data, with a population of 132 MSMEs collected under the auspices of the Rahmatan Lil Alamin Nganjuk Islamic Boarding School. The sampling technique uses the slovin formula and a sample of 100 SMEs is obtained. Data collection techniques using a questionnaire. Data analysis uses instrument testing, model development through Structural Equation Modeling (SEM) and hypothesis testing. The results of the study show that using IT training is able to mediate the effect of intra collaboration and supply chain management on the market performance of MSMEs. MSMEs will experience an increase in market performance if the intra collaboration of each MSME group has high commitment, supply chain management is well managed, especially payment patterns that are communicated to provide convenience to fellow MSMEs, as well as using IT training that supports collaboration and the MSME supply chain.